PENGARUH BEBERAPA TIPE PENGGUNAAN LAHAN TERHADAP SIFAT KIMIA TANAH DI KECAMATAN WULA WAIJELU KABUPATEN SUMBA TIMUR - Teul, Matias Umbu; Killa, Yonce Melyanus; Ndapamuri, Melycorianda Hubi (Fakultas Pertanian, Program Studi Agroteknologi, 2024)
The availability of nutrients in the soil is also very important whether the soil conditions are low, medium or high. It is important to know the chemical properties of the soil, because they can be used as a basis for determining the type and dose of fertilizer. This research was conducted to determine the effect of land use on the chemical properties of soil in the Wula Waijelu subdistrict, East Sumba Regency. This research was conducted from December 2023 to January 2024. The methods used in this research were survey methods and laboratory analysis. Determining the sampling location was carried out using the purposive sampling method (done deliberately by looking at land use at the research location). The parameters observed were P-total, K-total, base saturation (KB), cation exchange capacity (CEC), pH, C-organic. The results of the research show that land use (rice fields, plantations/gardens, moors/farms and shrubs) does not have a real influence on soil chemical properties such as total P, total K, KB, CEC, pH and C-organic in Wulla Waijelu sub-district, Regency East Sumba. The shrub land use type gave the highest values for P-total (39.44 ppm), K-total (0.73 me/100 g), base saturation (KB) (75.04%). Cation exchange capacity (CEC) with the highest value in field land use, pH in neutral and alkaline conditions while C-organic with the highest value in paddy field use